2017
DOI: 10.1038/s41467-017-01928-z
|View full text |Cite|
|
Sign up to set email alerts
|

Ultrafast bridge planarization in donor-π-acceptor copolymers drives intramolecular charge transfer

Abstract: Donor-π-acceptor conjugated polymers form the material basis for high power conversion efficiencies in organic solar cells. Large dipole moment change upon photoexcitation via intramolecular charge transfer in donor-π-acceptor backbone is conjectured to facilitate efficient charge-carrier generation. However, the primary structural changes that drive ultrafast charge transfer step have remained elusive thereby limiting a rational structure-function correlation for such copolymers. Here we use structure-sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
95
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(100 citation statements)
references
References 71 publications
5
95
0
Order By: Relevance
“…As previously reported, it can also achieve long-distance charge separation between the donor and acceptor, thus ensuring a long-lived charge transfer state. [8] Fig. 1b exhibits the steady-state absorption spectra of the three polymers, the absorption spectra of the three polymers with different π bridges present similar shapes, featured by two distinct absorption bands.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously reported, it can also achieve long-distance charge separation between the donor and acceptor, thus ensuring a long-lived charge transfer state. [8] Fig. 1b exhibits the steady-state absorption spectra of the three polymers, the absorption spectra of the three polymers with different π bridges present similar shapes, featured by two distinct absorption bands.…”
Section: Methodsmentioning
confidence: 99%
“…[5] In consequence, OPV devices that consist of Donor-Acceptor alternating conjugated polymers could become the economically viable alternatives to Si-based solar cells. [6][7][8] The latest researches from various groups have shown that the e ciency of OPV can be improved by using low band gap conjugated alternating copolymers (as seen in PCDTBT, PBDTTT, and PTB families). [9][10][11][12] An important difference between these polymers is that the exciton transition at the lowest energy level exhibits partial charge-transfer characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…A dual fluorescence is often achieved through the structural equilibrium between the locally excited (LE) state and the relaxed ICT state (Figure a) . The extent of the LE and the ICT emission can easily be modulated by varying the substituents, steric restrictions, and polarity of the local environment of the probe . Hence, D‐A based fluorophores have become popular in the last few years to achieve white light emission .…”
Section: Panchromatic Emission Through Charge Transfermentioning
confidence: 99%
“…Heterostructures in polymers (or copolymer configurations) enrich their functionalities, and numerous works have studied organic polymers that feature random ( 1 4 ), block ( 5 14 ), and sequence-controlled ( 15 21 ) copolymer compositions. For example, Roy et al .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Roy et al . ( 14 ) reported a fundamental intramolecular charge-transfer mechanism for donor-π-acceptor copolymers, which led to the fabrication of energy-efficient organic solar cells. Researchers have also developed supramolecular copolymers based on noncovalent bonds such as hydrogen bonds, metal coordination bonds, and π-π interactions ( 22 30 ).…”
Section: Introductionmentioning
confidence: 99%